ATR–FTIR, a new tool to analyze the oligomeric content of Aβ samples in the presence of apolipoprotein E isoforms. Issue 3 (2010) - Cerf, Emilie; Ruysschaert, Jean-Marie; Goormaghtigh, Erik; Raussens, Vincent
Abstract : Alzheimer̕s disease (AD) is a neurodegenerative disorder caused by the aggregation of the amyloid-beta peptide (A β ), leading to amyloid plaques deposition in the brain. Although A β aggregation pathway still remains unclear, recent studies point out the enhanced toxicity of oligomers compared to fibrils. The E4 isoform of apolipoprotein E (ApoE) is the major risk factor in AD as people carrying one ɛ4 allele have significantly higher chances to develop the disease. Nevertheless, this phenomenon is still poorly understood. Our group has shown that attenuated total reflection Fourier-transform infrared spectroscopy (ATR–FTIR) could discriminate between A β 42 oligomers and fibrils. Indeed, oligomers display anti-parallel β-sheet spectral components while fibrils are characterized by a parallel β -sheet organization. Using those spectral features to analyze the oligomeric content of our samples, we studied the influence of ApoE on A β 42 aggregation. Our experiments demonstrated that ApoE3 increased the amount of A β 42 oligomers in the sample. We can thus determine the proportion of A β oligomers in the presence of another compound in the sample. We plan to use ATR–FTIR to assess the effects of the other isoforms of ApoE on A β aggregation. Moreover, this could be extended to study the influence of other molecules or proteins on A β aggregation.